(3EOGQI GdehGQO GdHTQjI (B:s (3eaGgje hJhLgGJ eYGUQI (B/s - (3GdRHjOj, Zfj OMGe JfGjs; (3GdRjOj, fGXe LhGO YHO SdeGfs ((3YeGf(B: s (3OGQ GdMGeO ddfTQ hGdJhRjY(B, s, 2018)
(3jVe eGgjI hfTCI hJWhQ EOGQI GdehGQO GdHTQjI, eONd eYGUQ dOQGSI EOGQI GdehGQO GdHTQjI, eOjQ GdehGQO GdHTQjIESJQJjLjI EOGQI GdehGQO GdHTQjI, JNWjW GdehGQO GdHTQjI, JMdjd hJUeje GdhXjaI, JNWjW GdehGQO GdHTQjI, GSJbWGH GdehGQO GdHTQjI, GNJjGQ GdehGQO GdHTQjI, JfeHI hJWhjQ GdehGQO GdHTQjI, EOGQI GdeSGQ GdhXjaj, Jbjje COGA GdYGedjf, JOQjH hJWhjQ GdehGQO GdHTQjI, JYhjV GdehGQO GdHTQjI hecGaCJgG, JMajR GdehGQO GdHTQjI, JYhjV GdehGQO GdHTQjI, GdUMI hGdSdGeI, EOGQI GdehGQO GdHTQjI aj EWGQ HjFI GdYhdeI, fXGe eYdheGJ GdehGQO GdHTQjI, EOGQI GdehGQO GdHTQjI GdCdcJQhfjI, ehVhYGJ eYGUQI aj OQGSI GdehGQO GdHTQjI, QCS GdeGd GdHTQj, EOGQI GdehgHI, GdebOQGJ GdLhgQjI ddehGQO GdHTQjI, EOGQI GdLhOI GdTGedI ddehGQO GdHTQjI, GdejRI GdJfGaSjI GdeSJfOI ddehGQO GdHTQjI(B.s
(3HjHdjhZQGajG(B: (3U U(B.551-599s
Keywords: (3EOGQI GdCaQGOs; (3Gdbhi GdYGedIs